Business Models and Opportunities Recognition - Jowita TRZCIELINSKA; Renata KAPS (Communications of International Proceedings, 2021)
In an environment characterized by different intensity of changes occurring in it, different business models are used. The literature indicates that in a turbulent and unpredictable environment, the appropriate organizational strategy is that of an agile enterprise, i.e. an enterprise oriented at seeking and exploiting market opportunities. It is therefore reasonable to ask whether market opportunities are involved into enterprise business models and whether such enterprises perform better than these which do not recognize opportunities? There is an extensive literature discussing business models (Osterwalder A, 2004; Chesbrough H. 2010; Bock, AJ & George, G. 2011),  and enterprise agility (Goldman S., Nagel R., Preiss K. 1995; Zhang Z., Sharifi H. 2000; Cunha M.M.C., Putnik G.D. 2006) as well as opportunity recognition issue (Ardichvili et al, 2003; Baron R.A, 2006; Kirzner, I.M. 2008; Bruks I. et al, 2011). However, it does not provide an answer to the question posed above. Answering this question may provide indications by which business models are better suited to take advantage of opportunities arising in an environment. In order to obtain an answer to this question, research has been conducted on a sample of 150 small (excluding micro), medium and large enterprises operating in Poland. The research used the definition of business model developed by Chesbrough and Rosenbloom (2002). The achieved results indicate that the stronger the correlation between opportunity recognition and business model factors, the higher the turnover of enterprises.
Keywords: Business Model; Agile Enterprise; Opportunity Recognition; Turbulent Environment.